Pengalihan Sebagian Gaji Tenaga Pendidik Sebagai Voucher Belanja di Sakinah Mart Pada Masa Pandemi Covid-19 - Ahmad Taufan; Ahmad Rifai (Ulumul Syar'i : Jurnal Ilmu-Ilmu Hukum dan Syariah, 2021)
In the ijarah transaction (wages) there are conditions that must be met, including thewillingness between the two parties (mu'jir and musta'jir). However, in the case ofthis study, the researcher found several respondents who objected or were not willingwhen their salaries had to be transferred. After the researchers studied this case, theresearcher concluded that the root of the problem so that the educators objected wasdue to the uneven notification of transfers to educators and the high cost of somegoods at Sakinah Mart.